The REVAMP natural experiment study: the impact of a play-scape installation on park visitation and park-based physical activity - Jenny Veitch; Jo Salmon; David Crawford; Gavin Abbott; Billie Giles-Corti; Alison Carver; Anna Timperio (BMC, 2018)
Abstract Background Designing parks that optimise visitation and support visitors to be active is important for public health. Yet there is very little evidence about whether playground refurbishment achieves these objectives. This study examined the impact of the installation of a play-scape in a large metropolitan park in Melbourne, Australia. Methods Natural experiment study (intervention vs control). At both parks, park visitation and physical activity were assessed before (T1, 2013) and after the intervention at 12 (T2, 2014) and 24 months (T3, 2015). At each time point, measures included: observations of park visitors using the System for Observing Play and Recreation in Communities on four weekdays and four weekend days, objective monitors to record usage of the walking paths and the number of cars entering the park; and intercept surveys with adult park visitors. Cross-sectional surveys were conducted with local residents at T1 and T3. Results The observational data showed a 176% increase in park visitor counts from T1 to T2 (Incidence Rate Ratio (IRR) = 2.76, 95% CI = 1.04-7.33), at the intervention park relative to the control park. The intervention park had a 119% increase in counts of visitors observed engaging in MVPA from T1 to T2 (IRR = 2.19, 95% CI = 1.14-4.20), and a 128% increase from T1 to T3 (IRR = 2.28, 95% CI = 1.19-4.38), relative to the control park. The relative increases in visitation  at the intervention park play-scape compared with the control park playground were highly statistically significant from both T1 to T2 (IRR = 18.12, 95% CI = 5.51-59.59) and T1 to T3 (IRR = 15.05, 95% CI = 4.61-49.16). Similarly, there was a significant interaction between time and park with regard to the number of visitors observed engaging in MVPA in the play-scape/playground areas. The intercept survey data showed an increased odds of children's regular visitation to the intervention park at T2 (OR = 2.67, 95% CI = 1.08, 6.64), compared with T1, relative to the control park. The remaining results from the intercept survey, objective monitors and resident surveys showed no significant differences in visitation between the two parks. Conclusions These findings confirm that a well-designed play-scape installation has the potential to increase park visitation and encourage visitors to be physically active. Trial registration Current controlled trial ISRCTN50745547 .